Finite life fatigue design of spiral springs of dual-mass flywheels: Analytical estimation and experimental results. (June 2018) - Maffiodo, Daniela; Sesana, Raffaella; Paolucci, Dino; Bertaggia, Sabrina
A procedure to design the spiral springs finite life for dual-mass flywheels is presented. Due to design constraints, installation space, production processes, stiffness requirement, maximum torque, and maximum speed, these components are dimensioned for finite life. Two- and three-dimensional finite element model static structural analysis was performed to obtain the stress distribution, deformed shape, and to validate optimization design. The fatigue analysis was performed both experimentally and by means of a component life estimation model. An experimental duty cycle was applied. Finite element analysis and experimental analysis agree in pointing out the location and the value of maximum stresses and the shape of deformation. Vehicle tests highlight premature spiral springs' failures, which do not agree with life estimation. The examination of the fracture showed that fretting and wear, along with fatigue phenomena, are the causes of premature failures. A dedicated component life estimation model is required, taking into account of wear and loading history.